How to Note : A Framework for the Assessment of Fiscal Decentralization System - Yilmaz, Serdar; Aslam, Ghazia; Gurkan, Asli (World Bank, Washington, DC, 2012)
Fiscal decentralization provides the link between incentives for better performance of the local government and the elected support from the citizens and is, therefore, essential for an effective system of decentralization. The purpose of this note is to elucidate components of a well-designed fiscal decentralized system and is aimed to assist task teams and stakeholders to evaluate fiscal decentralization effort in any given country. There are two main components of fiscal decentralization system: a) discretion of the local government to make decision on fiscal matters (including revenue assignment for local goods, revenue generation, transfer of funds through a well-designed transfer system, and utilization of funds); and b) accountability including mechanisms that hold local government officials to other elected and non-elected officials and social accountability that allows direct monitoring of the local government officials by the citizens.